Особенности относительной спектральной отражательной способности и различия высот облачных поясов Юпитера - Тейфель, В.Г.; Харитонова, Г.А. (Кинематика и физика небесных тел, 1991)
Анализ широтных вариаций относительного спектрофотометрического градиента по спектрограммам центрального меридиана Юпитера показал, что в темных облачных поясах SЕВ и NЕВ в отличие от светлых зон в диапазоне λλ 0.40—0.50 мкм этот градиент значительно меньше, чем в диапазоне λλ 0.50—0.68 мкм. Такая особенность подтверждается и данными фотоэлектрической спектрофотометрии [9]. Одно из возможных объяснений состоит в том, что эффективная верхняя граница облаков в темных экваториальных поясах лежит примерно на 15—20 км глубже, чем граница облаков в светлых зонах. The analysis of longitudinal variations of the relative spectrophotometric gradient using spectrograms of Jupiter’s central meridian has shown that in the dark belts SEB and NEB the gradient at λλ 0.40—0.50 μm is significantly smaller than at λλ 0.50—0.68 μm as distinct from the bright equatorial and tropical zones STrZ, NTrZ or polar regions. This peculiarity is confirmed by the comparison with photoelectric spectrometry data [9]. The numerical simulation of diffuse reflection spectra in terms of the model "cloud layer+the Rayleigh scattering in the overcloud atmosphere" can explain these effects by differences of the cloud top altitudes: the effective cloud boundary in dark belts lies about 15—20 km lower than in bright cloud zones.